Pengalaman Baby blues Syndrome Pada Ibu Postpartum di Kabupaten Merauke - Sitti Asma Kurniyati Laitupa; Endah Purwanti; Laili Nur Hidayati (Journal of Pharmaceutical and Health Research, 2023)
Background Postpartum blues, or better known as baby blues," is a mild mood disorder that is often experienced by mothers in the first week after giving birth and peaks on the third to fifth day. This can be triggered by a mother's feeling that she is not ready for the birth of a baby or by an awareness of the responsibilities of being a mother. Baby blues in Indonesia are experienced by many postpartum mothers, especially at-risk and primiparous mothers. Lack of public awareness regarding baby blues results in a lack of support given to mothers, making them feel neglected and alone. If the baby blues are not handled properly, they can progress to postpartum depression and postpartum psychosis. The purpose of this research is to find out the feelings of mothers who experience baby blues and their efforts to overcome them. This research method uses qualitative methods through a phenomenological approach. Participants were selected using a purposive sampling technique, followed by interviews with willing mothers. The results of this study found four themes: the feelings of mothers when experiencing baby blues; causal factors; efforts made by mothers; and expectations of mothers who experience baby blues. In conclusion, every postpartum mother is at risk of experiencing baby blues, and the best effort that can be made is to provide social support such as informational, emotional, instrumental, and assessment support.